2011
DOI: 10.1136/bmj.d1277
|View full text |Cite
|
Sign up to set email alerts
|

Improving child health services in the UK: insights from Europe and their implications for the NHS reforms

Abstract: The coalition government's Health and Social Care Bill is unlikely to deliver the improvements in children's health services that are urgently needed. Useful lessons can be learnt from how other European countries deliver healthcare for children, say Ingrid Wolfe and colleaguesThe care provided by UK children's health services is inferior in many regards to that in comparable European countries. Although there are many examples of good practice, health services too often provide poor outcomes and are seemingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 12 publications
(12 reference statements)
2
65
0
Order By: Relevance
“…37 Such failures likely contribute to the United Kingdom's relatively high child death rates from meningococcal disease, pneumonia, and asthma, where first-access services such as primary care are integral. 38,39 Diagnosis and assessment incidents tend to be a reflection of providers' skills and competencies and may be less likely to be reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Such failures likely contribute to the United Kingdom's relatively high child death rates from meningococcal disease, pneumonia, and asthma, where first-access services such as primary care are integral. 38,39 Diagnosis and assessment incidents tend to be a reflection of providers' skills and competencies and may be less likely to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,36,39 For example, most (75%) pediatric asthma-related hospital admissions are thought to be preventable with better primary care. 40 Our findings reflect the significant potential for harm to children that exists as a result of poor management and treatment of longterm pediatric conditions in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…147 The analysis of 'first contact models' in those countries with better child survival outcomes can provide useful insight into different ways of integrating healthcare across community and hospital boundaries. 141,148 The management of chronic childhood diseases such as asthma, diabetes, and epilepsy, requires a shift in focus from a hospital-centric model of provision to an integrated system that transcends arbitrary boundaries between primary and secondary care. Much might be lifted from the model of chronic care provision in the elderly with collaborative organisational arrangements between health and social services and supportive financial processes.…”
Section: Factors In Service Deliverymentioning
confidence: 99%
“…A recent analysis of WHO data identified higher mortality specifically in conditions that are influenced by health service provision such as meningococcal disease, pneumonia and asthma, and concluded that if the UK health system performed as well as that of Sweden, as many as 1500 children might not die each year. 6 There are several possible explanations for this, some of which illustrate weaknesses of health care provision for children in this country, and further work is needed to identify and respond to such gaps in care. While cross-country comparisons are fraught with difficulty, it is essential that we take such data seriously and use them as a stimulus to action.…”
Section: Child Mortality In England and Walesmentioning
confidence: 99%